Teknik Pemeriksaan Kegawatdaruratan Os Nasal Dengan Klinis Suspek Fraktur Di Instalasi Radiologi Rsi Siti Aisyah Madiun - Dea Desta Juni Lestari; Ike Ade Nur Liscyaningsih; Ayu Mahanani (Journal of Innovation Research and Knowledge, 2026)
Background: Nasal bone fractures are among the most common facial injuries, commonly caused by traffic accidents, sports injuries, or direct trauma. Radiographic examination is essential for confirming the diagnosis, particularly in non-cooperative patients, where examination techniques must be adapted to ensure patient safety and obtain optimal diagnostic images. Objective: This study aimed to describe the radiographic examination procedure of the nasal bone and explain the rationale for using the semiprone true lateral position in non-cooperative patients with suspected nasal bone fractures at the Radiology Department of RSI Siti Aisyah Madiun. Method: A qualitative case study approach was conducted from December 2025 to January 2026 involving three radiographers and one radiologist. Data were collected through observation, interviews, documentation, and literature review, then analyzed descriptively. Results: The examination required no special patient preparation except removing metallic objects from the head region. Radiography was performed using a lateral projection in the semiprone true lateral position with exposure factors of 65 kV, 200 mA, and a focus-to-film distance of 100 cm. This positioning was selected because the patient was weak and unable to follow instructions, providing greater safety and comfort during the examination. The lateral projection clearly demonstrated the nasal bone anatomy and fracture line without requiring additional projections. Conclusion: The semiprone true lateral position is an effective radiographic technique for evaluating suspected nasal bone fractures in non-cooperative patients, providing adequate diagnostic information while improving patient safety and examination efficiency